Nurse attitudes toward caring for older patients with delirium - Hagerling, Faye L., author; Fruhauf, Christine A., advisor; MacPhee, David, committee member; Dik, Bryan, committee member (Colorado State University. Libraries, 2015)
Delirium, which is prevalent among older hospitalized patients, is a disease that may be prevented or reversed with appropriate care. However, the consequences of not adequately treating delirium in a growing older population can be enormously costly to patients, families, nurses, and the greater healthcare system. Effective delirium care is multifactorial. An important aspect of care is nursing attention to changes in the patient and follow-through with timely treatment. The purpose of this study was to examine nursing staff attitudes in caring for older patients with delirium before and after an educational training on delirium. The study took place at a community hospital and included participants from the medical, orthopedic, and surgical units. Along with demographic questions, the survey questions and several open-ended questions asked participants about their attitudes toward: (a) general care for patients 65 years and older, (b) perceived knowledge, competence, and confidence in caring for older patients with delirium, (c) time and support in caring for older patients with delirium, (d) personal impacts in caring for older patients with delirium, and (e) personal beliefs regarding aging and health. The results of the survey showed significant positive change with two identified components of care: (a) knowledge, competence, and confidence and (b) ability to identify delirium and understand its consequences. Several personal impacts, such as feeling overwhelmed, also positively changed after the intervention. However, participants reported a continuing need for more time and support in caring for older patients. Philosophies of aging were not changed. The survey may be a beginning for further development in assessing nurse attitudes toward care for older patients with delirium and the contribution of personal impacts and beliefs to that care.